The Psalter, or, Psalms of David in the language of the Cree Indians of north-west America [electronic resource] - Horden, John, 1828-1893. ([London] : Printed for the Society for Promoting Christian Knowledge, 1875)
Electronic reproduction. Mode of access: Internet. 44